Evaluation of egm2008 using GPS/LEVELING data in Thailand - Dumrongchai P. (2017)
The non-tidal EGM2008 geopotential geoid model has been compared with 258 GPS heights co-located with orthometric heights in Thailand (in the ITRF2005(2008) and the national Kolak vertical datum of 1915 (Kolak-1915)). The comparisons show a 1.012-m root mean square (rms) with a mean offset of +0.997m. A north-south tilted plane of about 0.135 ppm [or mm/km] is also evident in the differences in the whole area of the country, whereas there is no appreciable east-west tilted plane. Considering separated north and south areas reveals the tilts of about 0.136 ppm and 0.352 ppm. Importantly, because of good quality of GPS heights, these disagreements (assumed to be errors) are possibly in one or all of EGM2008 and Kolak-1915 datum deficiencies.